Power asymmetry and value creation in B2C relationship networks - Marcin Wieczerzycki (International Journal of Management and Economics, 2021)
The purpose of this paper is to explore the problem of power distribution within networks of relationships between companies and consumers (business-to-consumer (B2C) networks) and to examine the ways in which value is created and captured in such structures. To this end, we applied the network approach to multiple theoretical constructs describing collective consumer phenomena, carried over from the field of sociology to management science. Based on the literature and case study analysis, we managed to define a typology of B2C networks consisting of three types: (1) publics - centered around and dominated by a company, with no relationships between consumers themselves, creating value through crowd-sourcing; (2) communities - also centered around a company, but independent to a degree and more focused on consumer-to-consumer (C2C) relationships, creating value through consumer-managed projects; and (3) tribes - where companies serve only as peripheral actors, and their products - as potential symbols of affiliation, with value being created through creation and reinterpretation of the said products' meanings (sign value).
Keywords: D85; M31; Z13; D26; 650; B2C relationships; B2C networks; consumer behavior; consumer communities; value creation